2021
DOI: 10.3389/fevo.2021.733974
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Annual Wood Formation of Cryptomeria fortunei and Cunninghamia lanceolata in Humid Subtropical China

Abstract: Monitoring cambial activity is important for a better understanding of the mechanisms governing xylem growth responses to climate change, providing a scientific basis for tree-ring-based climate reconstructions and projections about tree growth under future climate scenarios. It plays an even more important role in investigating evergreen tree growth in regions with less distinct seasonal cycles. Subtropical evergreen forests have been studied in recent years for their sensitivity to climate change, but it rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 84 publications
1
4
0
Order By: Relevance
“…began in March and ceased in November. The growth duration was prolonged by 3-4 months compared to coniferous species in cold environments (Rossi et al, 2016) but was consistent with the findings of Huang et al (2018) and Zheng et al (2021) who reported that the regional climate plays a significant role in wood formation processes of subtropical conifers. A humid and warm climate is optimal for leaf photosynthesis, which will further promote the radial growth of trees (Ding et al, 2021).…”
Section: Dry and Hot Summer Climate Induces Bimodal Growthsupporting
confidence: 90%
See 2 more Smart Citations
“…began in March and ceased in November. The growth duration was prolonged by 3-4 months compared to coniferous species in cold environments (Rossi et al, 2016) but was consistent with the findings of Huang et al (2018) and Zheng et al (2021) who reported that the regional climate plays a significant role in wood formation processes of subtropical conifers. A humid and warm climate is optimal for leaf photosynthesis, which will further promote the radial growth of trees (Ding et al, 2021).…”
Section: Dry and Hot Summer Climate Induces Bimodal Growthsupporting
confidence: 90%
“…Microcores were collected from both the CW (the widest tree rings) and the OW (the narrowest tree rings) (as seen in Supplementary Figure 2). Each core had a diameter of 2 mm and a length of 2-3 cm that contained at least two intact xylem and lamellar bands with adjacent phloem ( Zheng et al, 2021). To maximize the use of limited sampling locations and minimize influences between adjacent sample areas, samples were taken in a zigzag pattern around the trunk, with a minimum distance of 5 cm between each sample (Supplementary Figure 3).…”
Section: Tree Selection and Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The field tree growth monitoring research conducted at the GM study site shows that the cambium cells of Cryptomeria fortunei begin to expand around April, and the entire lignification process ends around November (Zheng et al 2021). Combined with dendrometer data, we determined that the entire growing season of Cryptomeria fortunei in the study site is approximately from April 6th to November 5th each year, of which June 15th is the dividing line between earlywood and latewood.…”
Section: Stable Carbon Isotopic Analysismentioning
confidence: 96%
“…2 and Fig. 7c), the stomata of Cryptomeria fortunei trees would close (Gan et al 2017;Guo et al 2018;Zheng et al 2021), resulting in the decrease of Ci, and finally leading to the increase of iWUE (Tei et al 2014) (Eq. 5).…”
Section: The Iwuemes and Iwuetra At The Study Sitesmentioning
confidence: 99%